Improving the inventory management in PT Integra Indocabinet supply chain - Indira Esantya Amalia; Jorge Luis Siesquen Deza; Ahmad Al Fahad (Journal of International Conference Proceedings (JICP), 2018)
Integra Group is one of Indonesian largest vertically integrated wooden products manufacturer. It was established in 1989 and based in Sidoarjo – East Java. Moreover, Integra Group consists of 8 companies: 5 manufacturing companies (including an indirect subsidiary), 1 distribution company, 2 forestry concession companies and a non-operating holding company, which are fully consolidated under Integra Group. One of those subsidiary is PT Integra Indocabinet that its in charge of manufacturing process. The company produces and sells wooden furniture and other wooden products in the indonesian market and exports its products to the United States, Canada, and Europe. Every month they are able to export in the range of 300 400 containers.The company’s products include indoor furniture, bedroom/casegood furniture, panel furniture, and building components. It also holds forest concession rights. Even though PT Integra Indocabinet have been working in a good way, they are having some troubles about two things: overproduction and defective products, both problems increase the inventory cost and harms its efficiency. Therefore, in order to solve those issues we plan to make demand forecasting analysis through inventory management and apply some lean techniques to avoid shrinkages. That is the main reason why we firmly believe that both problems are inside the company supply chain. Keywords : Supply chain management, overproduction, efficiency, shrinkages, demand forecasting, Indonesia, inventory cost, lean techniques.